De las locas bobas a las falsas mujeres. El personaje transgénero en la prensa antioqueña, 1890-1980 (2018)
ABSTRACT: This paper explores the ways how written press represented and interpreted male transgender subjects, throughout a ninety-year period, showing how this undecipherable figure, who turned to humor and simulation to make a social link possible, was turned into a targeted subject, through contents depicting a false, degenerate, outlaw, violent persona, who was detached from social world. In short, newspapers painted a dangerous character, who should be corrected and confined. This reading on the contents of press written between 1890 and 1980, refers mainly to El Colombiano, El Correo, and Sucesos Sensacionales newspapers, in which we could identify a rendering of this abject social subject in images and texts.